“Beware of Pity”: On the Insidious Role of Pity in Private and Public Life (Politeja, 2023)
The title of this article alludes to the famous novel by Stefan Zweig Ungeduld des Herzens (translated into English as “Beware of Pity”). The novel illustrates the destructive role that pity plays in our private life, but, as will be argued in the article, the role of pity can be equally destructive in public life. The first part of the article has a conceptual character – the distinction is made therein between two types of pity: (1) as “the heart’s impatience (Ungeduld des Herzens)” to “rid itself as quickly as possible of the painful experience of being moved by another person’s suffering (Stefan Zweig, Beware of Pity, p. 19)”; and (2) as a mixture of contempt towards the sufferer and increased sense of one’s own power. What these two types of pity have in common is that they are self-regarding, that is, not having as its ultimate aim the well-being of the suffering person, and in fact preserving distance to the sufferer. This feature distinguishes them from compassion – a truly other-regarding fellow-feeling with the sufferer. The second part of the article, inspired by Zweig’s novel, will trace the negative consequences of pity in our private lives. The third part will strive, first, to reconstruct Hannah Arendt’s argumentation (presented in her book On Revolution) for her critical evaluation of pity as a political emotion, and secondly, to develop it in some new directions (inter alia, drawing on the above distinction between two types of pity, which is absent in Arendt’s analysis). Finally, it will be argued that even though in private life empathy (broadly understood) does not have to take the form of pity (it often assumes the laudable form of compassion), it is almost bound to take the form of pity in political life. If this claim is true, it means that one needs to treat with much caution the oft-made postulates of increasing the role of ‘empathy’ in public life.